The Student's Perception and Motivation of Using Infographicd for Learning English - Hilmi, Muhummad Ainul; Syam, Ummi Khaerati; Ariana (Journal of Computer Interaction in Education, 2020)
This research has objectives to know the Students' Perception and Motivation in Using Infographics for Learning English . This research generally answers two questions as: (1) What are students‟perception in using infographics for learning english? and (2) How are students‟ motivation in using infographics for learning english.This study shows that students' perception and motivation in using infographics are high, as seen by each statement concerning the students' questionnaire responses.Based on the findings of the study, it can be concluded that students' responses and comprehension of infographics are high, and that their motivation to learn English is also high